1999
DOI: 10.1016/s0014-5793(99)00037-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of a novel photosystem II‐associated carbonic anhydrase in photosynthetic carbon assimilation in Chlamydomonas reinhardtii

Abstract: Intracellular carbonic anhydrases (CA) in aquatic photosynthetic organisms are involved in the CO P -concentrating mechanism (CCM), which helps to overcome CO P limitation in the environment. In the green alga Chlamydomonas reinhardtii, this CCM is initiated and maintained by the pH gradient created across the chloroplast thylakoid membranes by photosystem (PS) II-mediated electron transport. We show here that photosynthesis is stimulated by a novel, intracellular K K-CA bound to the chloroplast thylakoids. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 12 publications
(55 reference statements)
0
49
0
Order By: Relevance
“…As Cah-3 is known to be associated with polypeptides of photosystem (PS) II of C. reinhardtii thylakoid membranes (Park et al, 1999;Villarejo et al, 2002), it was necessary to be sure that the signal observed in the cell envelope fraction of M. chthonoplastes did not result from cross-contamination of this fraction with thylakoid membranes from the cyanobacterium. Antibodies against D1 (PsbA), a major protein of PS II, was used as a specific marker for thylakoid membranes (Nishiyama et al, 2001).…”
Section: Identification Of M Chthonoplastes Extracellular A-camentioning
confidence: 99%
“…As Cah-3 is known to be associated with polypeptides of photosystem (PS) II of C. reinhardtii thylakoid membranes (Park et al, 1999;Villarejo et al, 2002), it was necessary to be sure that the signal observed in the cell envelope fraction of M. chthonoplastes did not result from cross-contamination of this fraction with thylakoid membranes from the cyanobacterium. Antibodies against D1 (PsbA), a major protein of PS II, was used as a specific marker for thylakoid membranes (Nishiyama et al, 2001).…”
Section: Identification Of M Chthonoplastes Extracellular A-camentioning
confidence: 99%
“…CAH3 is not a membrane spanning protein as it can be released into the soluble fraction by washing the thylakoids with 200 mm KCl. Results by Park et al (1999) indicate that CAH3 is associated with photosystem II (PSII) particles but this needs to be further confirmed. To date there is no firm data to support a thylakoid localiza-tion for CA in any other higher plant or alga (see also below under unresolved questions).…”
Section: Thylakoid Membranementioning
confidence: 99%
“…Although CA activity can be detected in isolated PSII-enriched membranes from higher plants, the critical experiments showing that this activity is not due to a contamination by stromal CA still need to be done. Recent experiments demonstrating an association between the lumenal a-CA and PSII in C. reinhardtii (Park et al 1999) have led to a renewed discussion of existence of a similar a-CA in higher plants.…”
Section: Unresolved Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotic algae, chloroplastic CAs are thought to be required to supply CO 2 to Rubisco in the stroma and/or the pyrenoid where the predominant species of inorganic carbon is HCO 3 Ϫ because of the alkaline conditions of the stroma (Badger and Price, 1994). As a mechanism to enhance the rate of CO 2 supply to Rubisco in C. reinhardtii, it has been suggested that ␣-type CA (Cah3) is associated with photosystem II at the lumenal side of the thylakoid membrane and catalyzes the dehydration of HCO 3 Ϫ in the lumen to give an ample efflux of CO 2 to the stroma or the pyrenoid (Karlsson et al, 1998;Park et al, 1999, Moroney et al, 2001. These data clearly indicate that intracellular CA plays a key role in the CCM when it functions in particular cellular locations.…”
mentioning
confidence: 99%